Proceedings of the Sixth International Conference on Green and Human Information Technology ICGHIT 2018 - Hwang, Seong Oun.; Tan, Syh Yuan.; Bien, Franklin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume presents the Proceedings of the Sixth International Conference on Green and Human Information Technology (ICGHIT), held in Chiang Mai, Thailand, Jan 31-Feb 2, 2018. ICGHIT is the unique global conference for researchers, industry professionals, and academics interested in the latest development of green and human information technology. Its broad scope ranges from electronics to communications, computers, multimedia and signal processing, control and intelligent systems, IC and convergence technologies, which are related to green and human issues such as energy saving and human welfare. Specially in this volume, ICGHIT covers state-of-the-art technologies for the 4th industrial revolution, for example, cyber security, big data and cloud service, smart medical system, machine learning and its applications.
1. AMQP-Based Subscription Group Message Delivery System Design for Laboratory Safety System (by Hyun-seong Lee, Jae-gwang Lee, Jae-pil Lee, Ki-su Yoon, Woo-chang Kwon and Jae-kwang Lee) -- 2. Attack Probability Analysis on the MTD System (by Jang-Geun Ki and Kee-Young Kwon) -- 3. Extraction Efficiency of Three-Striped LED (by Kee-Young Kwon and Jang-Geun Ki) -- 4. Performance Comparison of Internet 4G Service Providers in Bangkok, Thailand (by Suttisak Jantavongso and Sanon Chimmanee) -- 5. Performance Evaluation of LoRaWAN on Campus Environment (by Dong Hoon Kim, Jae-Seong Jo and Eun-Kyu Lee) -- 6. Performance of Nano-crystalline Inductive Couplers Applied to Ship Powerline Communication (by Kyung-Rak Sohn, Seung-Ho Yang and Jae-Hwan Jeong) -- 7. Analysis of Hardware Requirements for IoT Teaching Aids (by HyunChang Lee, KyuTae Lee, SeoIk Kang, KeunYoung Choi, WonSik Na and SungYeol Kwon) -- 8. Location Estimation Technique in Bluetooth Beacon Based Indoor Positioning Systems (by Jeong Hyun Yoon, Inah Chung and Ye Hoon Lee) -- 9. Fog Agents in Distributed Multi Agent System For Autonomous Energy Management (by Ui-Kyun Na, Young-Gon Kim, Jae-Seong Jo and Eun-Kyu Lee) -- 10. Building Entry Loss (BEL) Characteristics for Incident Angles and Measurement Locations from 3.5 to 24 GHz (by Young Chul Leer, Soon-Soo Oh, Jae-Won Choi, Hwa Choon Lee, Jong-Hyuk Lim, Dae-Hwan Yoon, Sung Won Park and Byung-Lok Cho) -- 11. Upgrade of Electronic Security Fence System by Reduction of Vibration Noise by Wind Effect (by Hiesik Kim and Odgerel Ayurzana) -- 12. Study of Semi Deterministic Model for Fifth-Generation (5G) Wireless Networks (by Supachai Phaiboon and Pisit Phokharatkul) -- 13. Development of Integrated Monitoring System based on IoT for Odor Reduction (by Hye-Young Kim) -- 14. Classifying News Articles using Feature Similarity K Nearest Neighbor (by Taeho Jo) -- 15. A Knowledge Mining and Ontology Constructing Technology Oriented on Massive Social Security Policy Documents (by Gang Liu, Lian Sun and Weiping Fu) -- 16. Detection of GUI Elements on Sketch Images Using Object Detector based on Deep Neural Networks (by Young-Sun Yun, Jinman Jung and Seongbae) -- 17. Emotion and Fatigue Monitoring using Wearable Devices (by Jong-Seok Lee, You-Suk Bae, Wongok Lee, Hyunsuk Lee, Jinkeun Yu and Jong-Pil Choi) -- 18. Process and Evaluation Index of Bankart Surgery for the Simulator Development (by Min-Jae Lee, Ein Jeong Hwang and Do Hoon Oh) -- 19. Application of Use cases for Congestive Heart Failure (by Hyo Seon Kim, Ein Jeong Hwang, Sam Lee, Deok Kyu Cho and Do Hoon Oh) -- 20. Epileptic seizure detection using Empirical Mode Decomposition based fuzzy entropy and Support Vector machine (by Deepti Tripathi and Navneet Agrawal) -- 21. Preliminary Study on Wearable Patch Device with EHG Envelope Peak as Feature Parameter for Preterm Birth Monitoring (by Young Chang Jo, Hyuck Ki Hong, Hae Na Kim, Won Hee Hwang, Yeon Shik Choi and Suk Won Jung) -- 22. Study of Seizure Monitoring System Using Frontal Pole EEG Patch Device (by Haena Kim, Won Hee Hwang, Hyuck Ki Hong, Yeon Shik Choi, Suk Won Jung and Young Chang Jo) -- 23. Association analysis of Postoperative Hypothermia for Stability of Blood Pressure (by Hoon Jin and Yong-Gyu Jung) -- 24. Analysis of the Protection Circuit in the Function Generator for Education (by SungYeol Kwon, HyunChang Lee, KyuTae Lee, HyunMook Cho and SangYep Nam) -- 25. Development of DC Smart Plug Control System (by Narakorn Songkittirote, Worajit Setthapun, Kobsak Sriprapha and Hathaithip Ninsonti) -- 26. Decorrelation of Wireless Channel Coefficients for Secret Key Generation (by Xiaofu Wu, Dongming Dai, Xunjian Yu and Jun Yan) -- 27. Geo-Crowdsourcing and Map-Based Reporting for Smart Government (by Joseph Nathanael Witanto and Hyotaek Lim) -- 28. The LXC-LXD Virtualization in ARM64bit X-Gene2 Server (by Jin-Suk Ma, Dong-Jae Kang and Hak-Young Kim) -- 29. Mobile forged app identification system with centralized signature self-verification method (by Hyung-Woo Lee and Jaekyu Lee) -- 30. Implementation of Security Mechanism in IIoT Systems (by Minjeong Shin, Jihyeon Woo, Ibrahima Wane, Sungun Kim and Heung-Sik Yu) -- 31. An efficient searchable encryption scheme in the multi-user environment (by In Tae Kim, Tran Hai Quan, Ly Vu Duc, Trong Kha Nguyen and SeongOun Hwang) -- 32. Verification test of Cloud PaaS (PaaS-TA) on microserver (by Byung-Kwon Jung, Zi-Ho Shin Hyuk-je Kwon, Jin-Suk Ma, Hag-Young Kim and Dong-jae Kang) -- 33. Development of DC Smart Plug Control System (by Narakorn Songkittirote, Worajit Setthapun, Kobsak Sriprapha and Hathaithip Ninsonti) -- 34. The application of IoT technology in monitoring odors in industrial areas: The case of Sasang Industrial Area in Busan (by Ji-in Chang) -- 35. The Development of Smart Farm with Environmental Analysis (by Panupong Tanomkiat, Kobsak Sriprapha, Hathaithip Sintuya, Nuttiya Tantranont and Worajit Setthapun) -- 36. Multi-modal Sensor Calibration Method for Intelligent Unmanned Outdoor Security Robot (by Taeyoung Uhm, Gi-Deok Bae, JongDeuk Lee and Young-Ho Choi) -- 37. User Controls in Video Regeneration System (by Young-bong Kim, Yoseph Yoon, Keon-kuk Park, Oh-Seok Kwon and Jongnam Kim) -- 38. An Evaluation to Firmware Code Materials for Embedded IoT Device (by KyuTae Lee, HyunChang Lee, Sung Yeol Kwon, Sangyep Nam and DoHyeun Kim) -- 39. Faces Recognition using HAARCASCADE, LBPH, HOG And Linear SVM Object Detector (by Jae Jeong HWANG, Young Min Kim and Kang Hyeon RHEE) -- 40. Analysis on Signal Transmission Methods for Rapid Searching in Active SONAR Systems (by Woo-Sung Son, YoungKwang Seo, Wan-Jin Kim and Hyoung-Nam Kim).
Keywords: Telecommunication; Computer networks .; Big data; Computational intelligence; Communications Engineering, Networks; Computer Communication Networks; Big Data; Computational Intelligence